Evaluation of the diagnostic and prognostic potential of optical coherence tomography (OCT) of the pulmonary arteries during standardised right heart catheterisation in patients with pulmonary hypertension: a cross-sectional single-centre experience - Zeiger, Emilie; Jakob, André; Pozza, Robert Dalla; Fischer, Markus; Tengler, Anja; Ulrich, Sarah M.; Arnold, Leonie; Weismann, Constance G.; Schulze-Neick, Ingram; Haas, Nikolaus A.; Pattathu, Joseph (Cardiovascular diagnosis and therapy, 2023)
Pulmonary hypertension (PH) is diagnosed based on an invasive evaluation of the mean pulmonary artery (PA) pressure. The morphological assessment of the pulmonary arteries was only recently not feasible. With the advent of optical coherence tomography (OCT)-imaging, an accessible tool allows to study PA morphology longitudinally. The primary hypothesis was that OCT distincts the PA structure of PH patients from control subjects. The secondary hypothesis was that PA wall thickness (WT) correlates with the progression of PH. This is a retrospective monocentric study of 28 paediatric patients with (PH group) and without PH (control group) who had undergone cardiac catheterisation including OCT imaging of the PA branches. OCT parameters analysed were WT and the quotient of WT and diameter (WT/DM) and those were compared between the PH group and the control group. In addition, the OCT parameters were aligned with the haemodynamic parameters to evaluate the potential of OCT as a risk factor for patients with PH. WT and WT/DM in the PH group were significantly higher compared to the control group {WT: 0.150 [0.230, range (R): 0.100-0.330] 0.100 [0.050, R: 0.080-0.130] mm, P<0.001; WT/DM: 0.06 [0.05] 0.03 [0.01], P=0.006}. There were highly significant correlations between WT and WT/DM with the haemodynamic parameters mean pulmonary arterial pressure (mPAP) [Spearman correlation coefficient (r ) =0.702, P<0.001; r =0.621, P<0.001], systolic pulmonary arterial pressure (sPAP) (r =0.668, P<0.001; r =0.658, P<0.001) and WT and pulmonary vascular resistance (PVR) (r =0.590, P=0.02). Also, there was a significant correlation between WT and WT/DM and the risk factors quotient of mPAP and mean systemic arterial pressure (mSAP) (mPAP/mSAP) (r =0.686, P<0.001; r =0.644, P<0.001) and pulmonary vascular resistance index (PVRI) (r =0.758, P=0.002; r =0.594, P=0.02). OCT can detect significant differences in WT of the PA in patients with PH. Furthermore, the OCT parameters correlate significantly with haemodynamic parameters and risk factors for patients with PH. More investigations are required to evaluate to what extent the impact of OCT can contribute to the clinical care of children with PH.